The Relationship Between Self-Concept and Parents' Occupations in the Career Choices of Islamic Guidance and Counseling Study Program Students - Afnibar; Lestari, Kiki Elfi; Ummi, Ayunil; Rahmi, Aulia; Susanti, Meri (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
All students have career choices. This study aims to determine the relationship between self-concept and parental occupation in the students' career choices. This research method uses a quantitative method with a descriptive type. The population is final year BKI students with a sampling technique using random sampling technique, totaling 82 people. The instrument used is a questionnaire. The results of the study show that BKI Study Program students have a self-concept, as many as 75.61% are intellectual, 62.20% are able to socialize well, 79.27% are not easily angered or are able to control emotions well in socializing. Based on parental occupations, the majority are entrepreneurs as many as 43.90%. The most common career choices for students are one and two, namely: 54.88% want to be entrepreneurs and 12.20% as counselors. In conclusion, the choice of career students as entrepreneurs is very rational because they are intellectual and able to socialize well. This study has implications for the importance of preparing students with entrepreneurship courses and strengthening the Counselor profession.